Negotiating between forest conversion, industrial tree plantations and multifunctional landscapes. Power and politics in forest transitions. Issue 124 (August 2021) - Pichler, Melanie; Ingalls, Micah
Highlights: Power and politics are largely neglected in forest transition research. We develop a framework to identify power relations in forest politics. We analyze the contested forest transition in Lao PDR. Tree plantations and REDD+ gain importance to modernize extractivist activities. Livelihoods-based approaches should figure more prominently in forest politics. Abstract: Increasing forest cover through reforestation and forest regrowth constitutes an essential contribution to mitigating the climate crisis, especially in the tropics. The Southeast Asian country of Lao PDR is on the brink of a forest transition, that is, a shift from net deforestation to net increases in forest area. This process is, however, contested and this article sheds light to power and politics in forest transitions and the implications for forests and people in Lao PDR and beyond. We develop a conceptual framework rooted in political ecology and critical state theory to identify visions and strategies by institutional actors that aim to transform the forests in particular ways, reflect on their power resources and synthesize three development projects from these strategies. We identify an antecedent dominant extractivist development project, focused on state-led timber extraction and large-scale land acquisitions. We argue that green development strategies that commodify forests through offsetting schemes, results-based payments from REDD+ and industrial tree plantations are increasingly mobilized to complement and modernize this extractivist development trajectory. Whereas these strategies align in their focus on land sparing to intensify agricultural and forest production, on the margins, we carve out an alternative livelihoods-based development project that supports extensive agroecological practices (including shifting cultivation) and integrates forests into multifunctional landscapes, re-centering local interests in reforestation approaches. The research therefore contributes to a more complex understanding of power and politics in forest transition research as well as a nuanced understanding of forest politics in political ecology.